Onychomycosis Prevalence in Rice Farmers in Seginim District, South Bengkulu Regency. - Inayah Hayati; Rindy Marselina (ANJANI Journal (Medical Science & Healthcare Studies), 2021)
Onychomycosis is a common infection that occurs in the nail plate. Infections can be caused by the dermatophyte, non-dermatophyte or yeast groups of fungi. The fungus gets into the nails and causes thickening of the nails, leaving the nails glowing. The purpose of this study was to determine the prevalence of wetland farmers in Seginim Subdistrict, Bengkulu Selatan Regency infected with onychomycosis and to identify the types of fungi that cause onychomycosis in the nail scraps of rice farmers. This type of research uses descriptive cross sectional method with purposive sampling technique. The examination technique used direct preparations and culture in SDA media. The samples used in the examination were 40 samples of scraped nails of rice farmers in Seginim sub-district, South Bengkulu Regency. The results of this study showed that from 40 samples of nail scrapings that had the criteria of thickened, brittle, and yellowish brown nails, 16 samples were positive for Onychomycosis-causing fungi, namely 5 (12.5%) people infected with the fungus Trichophyton mentagrophytes and 11 (27.5%). ) people were infected with the fungus Trichophyton rubrum and 24 (60%) samples were negative.